Faction Oppression and Tris’ Resistance in Veronica Roth’s Insurgent - YOHANES WAHYUDI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2015)
Abstrak Sifat ingin berkembang pada manusia membawa setiap orang untuk bersaing satu sama lain . Hal ini dipengaruhi oleh tekanan yang berasal dari dalam diri manusia dan rasa tidak aman pada individu, disana tercipta situasi kerjasama yang kemudian dirumuskan menjadi hukum dan peraturan untuk menciptakan masyarakat yang stabil. Dalam perkembangannya, beberapa masyarakat atau suatu kelompok masyarakat melakukan suatu tindakan yang tidak menguntungkan bagi manusia lainnya yang mengakibatkan tindakan penindasan dan pemberontakan. Studi ini dilakukan untuk menganalisa perilaku manusia terhadap konsep penindasan dan juga pemberontakan terhadap masyarakat atau individu yang memberikan tekanan hidup atau suatu penindasan. Seperti yang disebutkan oleh Barker dalam konsep oppression yang menjelaskan bahwa penindasan terjadi jika seseorang atau sekelompok orang membatasi perilaku individu atau sekelompok masyarakat lainnya. Studi ini diproyeksikan terhadap novel Veronica Roth “INSURGENT” menggunakan istilah “divergent” sebagai subyeknya. The study is written by focusing on two questions: (1) how is faction oppression reflected in Tris in Veronica Roth Insurgent? And (2) what are Tris’ motif of resisting against the oppression in Veronica Roth Insurgent?. Analisis studi ini tentang seorang perempuan yang merupakan salah seorang dari divergent yang harus dimusnahkan sesuai anggapan Jeanine sebagai penguasa tertinggi dari faksi Erudite. Hingga suatu ketika perempuan tersebut harus merelakan banyak orang yang dia cintai untuk melindunginya dari pencarian Jeanine. Hidup secara nomaden yang dia lakukan adalah salah satu tindakan untuk mencari dukungan dari banyak orang. Hal ini bertujuan untuk melakukan pemberontakan terhadap pemerintahan Jeanine yang ingin melenyapkan orang yang dianggap sebagai Divergent. Hasil dari studi menunjukan penindasan yang dialami tokoh utama dan juga mengetahui tentang motif pemberontakan yang dilakukan tokoh utama tersebut. Keywords: Penindasan, pemberontakan Abstract Human nature wants to bring everyone to compete against each other. This is influenced by the human pressure and insecurity on the individual which has been created a situation of cooperation then formulated into laws and regulations to create a stable society. In the process of life, some people or a group of people perform an action that was not profitable to other humans which cause oppression and resistance. For that reason, this study was conducted to analyze the human behavior towards the concept of oppression and resisting against society or individuals who provide the pressures of life such as oppression. As mentioned by Barker in the concept of oppression, he explains that oppression occurs if a person or group of people restricts the behavior of individuals or a group of other people. The study is projected to Veronica Roth's novel "Insurgent" using the term "divergent" as the subject. The study is written by focusing on two questions: (1) how is faction oppression reflected in Tris in Veronica Roth Insurgent? And (2) what are Tris’ motif of resisting against the oppression in Veronica Roth Insurgent. This study is about the woman who called divergent that has to be destroyed. It is agreed by Jeannie’s perception who has a big authority of Erudite. She said that the people who are detected as the divergent, they have to move away from the life. Until the day moment, the woman must give up a lot of people that she loves to protect it from Jeanine’s search. Nomadic life that she did is one of the actions to look for support from the other people. This action is gathering people to resisting Jeanine’s governance who want to eliminate people that are considered as Divergent. The results of the study show the oppression experienced by the main character and also know about the motives of oppression by main character. Keywords: Oppression, Resistance